Model Business Letters, E-Mails & other Business. (Global Business Management Review (GBMR), 2022)
Shirley Taylor is a Communication Training Specialist andthe CEO of STTS Pte Ltd., a company well- known for its wide range of public, corporate and professional training workshops. Aa a trained teacher from the UK, she first took up a teaching post in Singapore in 1983 and had spent many years in the Asia Pacific region as a Training Consultant and Lecturer on secretarial and business studies courses. A trainer, speaker, author and editor, she has written and published 12 books on effective communication skills for university students, adults and working professionals. Her books are sold worldwide and have been translated into 6 major languages. She was also the 2011/ 2012 President of Asia Professional Speakers Singapore and is a member of the Global Speakers Federation. Apart from the book being reviewed for this article, she is also well- known for other titles which include: Communications for Business: A Practical Approach (Financial Times Management; 2005; 4thEd.), Success 365: 365 Great Ideas For Personal Development And Achieving Greater Success (Marshall Cavendish International (Asia); 2012) and Essential Communication Skills: The Ultimate Guide to Successful Business Communication (Management and Communication) (Longman; 2012). She currently lives in Singapore. She writes, shares, trains and motivates with the sole purpose of helping people to improve their communication skills that could help develop better relationship strategies in their workplace.